Improving Indonesian Language Literacy in A Diverse Local Community: A Case Study of the Level of Indonesian Language Proficiency of the Naulu Tribe in Central Maluku - Farid Yapono; Maruf Tehuayo; Junardin Muhamad Masihu (Al-Musannif, 2026)
This study aims to determine the improvement of Indonesian language literacy among the local community of the Naulu Tribe in Central Maluku. The research was conducted from July 8 to August 8, 2025, in Rohua Hamlet, Negeri Sepa, Amahai District, Central Maluku Regency, Maluku. The participants consisted of 35 members of the Naulu community. This study employed several research instruments, including tests, questionnaires, observations, and interviews. The test instrument consisted of a pre-test and post-test designed to measure Indonesian language literacy skills based on four indicators: reading, writing, listening, and speaking. Questionnaires were used to identify community responses after the implementation of the learning program, while observations focused on social interactions and language use in both educational and community settings. Interviews were conducted to identify challenges, causal factors, and community attitudes toward Indonesian language literacy. The data were analyzed using descriptive qualitative analysis and supported by Gain and N-Gain score calculations to measure literacy improvement. The findings showed significant improvements in all literacy indicators. Reading scores increased from 43.37 to 68.23, writing from 46.69 to 66.12, listening from 59.14 to 71.11, and speaking from 44.16 to 70.66. All categories improved from low to moderate levels. In general, literacy achievement increased from 11% in the initial literacy test to 34% in the final test, indicating a 23% improvement after the learning program. These findings demonstrate that the learning activities effectively improved the Indonesian language literacy skills and understanding of the Naulu community in Central Maluku.